Manajemen Standar Sarana Prasarana berbasis Total Quality Management (TQM) dalam meningkatkan kualitas pembelajaran (Studi kasus di SMPN 1 Purwakarta) - Deasy Nurmaulidah; Sadiyah; Nurlaeni; Waska Warta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The management of facilities and infrastructure is one of the factors that determine the success of educational implementation and the improvement of learning quality in schools. The availability of adequate facilities and a quality-oriented management system is essential to create an effective and conducive learning environment. This study aims to describe the implementation of Total Quality Management (TQM) in the management of facilities and infrastructure to improve learning quality at SMPN 1 Purwakarta. This study employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the management of facilities and infrastructure is carried out through needs-based planning, structured budgeting, and continuous preventive maintenance. Quality culture and the readiness of human resources support the successful implementation of TQM through the active involvement of all school members in maintaining and utilizing educational facilities. TQM-based management of facilities and infrastructure has contributed to improving learning comfort, enhancing the effectiveness of the learning process, and optimizing the utilization of educational facilities. This study concludes that the implementation of TQM in facilities and infrastructure management contributes to improving learning quality and the quality of educational services at SMPN 1 Purwakarta. Keywords: Total Quality Management, facilities and infrastructure, learning quality, educational management, educational quality.